Conocimiento y percepción de riesgo sobre COVID-19 en comercializadores del mercado de productores Iquitos 2021 - Tiznado Acosta, Maria Esther (2022)
The objective was to determine the association between knowledge and risk perception of COVID-19 in marketers of the Producers Market of the City of Iquitos, 2021. The study was Quantitative with a non-experimental, correlational and cross-sectional design, the population consisted of 74 marketers from 18 to 65 years of age of both sexes from the Producers Market of the city of Iquitos. The technique used was the interview, the instruments were the knowledge questionnaire about COVID-19 (Validity 98.3%) and reliability 96.4%), and the COVID-19 risk perception scale (Validity 94.6% and reliability (92.8%). The results: Regarding the knowledge of 74 (100%) of marketers, only 14 (18.9%) had correct knowledge about COVID-19, while 60 (81.1%) had incorrect knowledge about COVID-19; regarding the perception of risk about COVID-19, of 74 (100%) marketers, 67 (90.5%) had low risk perception over re COVID-19, while only 7 (9.5%) had a perception of high risk about COVID-19. It concludes in accepting the research hypothesis, that is, there is a significant statistical association between knowledge and perception of risk of COVID-19, in marketers of the Iquitos Producers Market, 2021 (p = 0.007; p < 0.05).